2016
DOI: 10.1002/bit.25927
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial optimization of CO2 transport and fixation to improve succinate production by promoter engineering

Abstract: To balance the flux of an engineered metabolic pathway to achieve high yield of target product is a major challenge in metabolic engineering. In previous work, the collaborative regulation of CO2 transport and fixation was investigated with co-overexpressing exogenous genes regulating both CO2 transport (sbtA and bicA) and PEP carboxylation (phosphoenolpyruvate (PEP) carboxylase (ppc) and carboxykinase (pck)) under trc promoter in Escherichia coli for succinate biosynthesis. For balancing metabolic flux to max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 48 publications
1
20
1
Order By: Relevance
“…pneumoniae when glycerol is used as the carbon source. Although succinate formation mainly occurs through the PEP carboxylation pathway in other bacteria (Sauer et al 1999;Yu et al 2016), the role of PEP carboxylation in the cell physiology and succinate formation of Kl. pneumoniae remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…pneumoniae when glycerol is used as the carbon source. Although succinate formation mainly occurs through the PEP carboxylation pathway in other bacteria (Sauer et al 1999;Yu et al 2016), the role of PEP carboxylation in the cell physiology and succinate formation of Kl. pneumoniae remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the ppc gene in the engineered E. coli strain SD121 ( △pflB , △ldhA and △ptsG ) led to 116.2 g L −1 of succinic acid with a yield as high as 1.13 g g −1 of glucose within 75 h . A combinative modification of introducing ppc, pck, bicA and sbtA genes as well as deletion of genes including pflB, ldhA and ptsG could increase succinic acid production effectively . It was also found that the disruption of ldhA and pflB genes (NZN111) would prevent the regeneration of NAD + from NADH, resulting in the loss of capability to grow anaerobically on glucose.…”
Section: Succinic Acid Production By Metabolically Engineered Strainsmentioning
confidence: 99%
“…Therefore, the PEP pool is very important in cellular succinate fermentation. The overexpression of endogenous or heterologous carbon dioxide fixing enzymes such as PEP carboxylase (encoded by the ppc), PEP carboxykinase (pck), pyruvate carboxylase (pyc), and malic enzymes (maeA and maeB) has been used for the overproduction of succinic acid (Millard et al, 1996;Lin et al, 2005b;Tan et al, 2013;Yu et al, 2016). PEP carboxykinase (encoded by the pck) of the rumen bacterium is critical in succinate production and anaerobic growth because it catalyzes the carbon dioxide fixation as well as the ATP formation (Lee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%